The Influence of Gerogi Animation Video Education (Toothbrushing Movement) on Toothbrushing Behavior in Class IV School Children at SD Negeri 3 Baktirasa South Lampung in 2024 - Fitri, Sabrina Aisya; Subardiah P, Ida; Puspita H, Richta (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The School Dental Health Program (UKGS) offers a practical solution to the dental health issues of children by offering instruction on motor skills, which includes the effective use of tooth brushing techniques. It is the objective of UKGS to enhance and preserve the dental and oral health of all students in schools by providing health education that involves health workers and dentists, as well as by educating students on the significance of maintaining dental and oral sanitation. The purpose of this investigation is to ascertain the impact of Gerogi Animation Video Education (Tooth Brushing Movement) on the tooth brushing behavior of Grade IV students at SD Negeri 3 Baktirasa, South Lampung in 2024. The quantitative method employed in this investigation is a pre-experimental design with a pretest-posttest sample size of one group. There were 54 students included in this investigation. For the Random Sampling technique, a sample of 48 students was selected from the population. After conducting statistical tests, it has been determined that the average value (mean) of children's capacity to brush their teeth was 8.40 prior to receiving health education and 11.21 subsequent to receiving health education. Bivariate analysis indicates that the provision of animated video education has a significant impact on the tooth hygiene behavior of grade IV students at SD Negeri 3 Baktirasa, South Lampung in 2024, with a p-value of 0.000. The findings of this investigation can be employed as a source of information to demonstrate that educational videos on dental brushing have an impact on the toothbrushing behavior of children and to broaden the selection of educational media in health education for elementary school children. It is anticipated that the UKS in schools will be able to deliver health education through the use of animated videos, which will be more engaging and simpler for students to comprehend.